Aplikasi Buluh Bambu untuk Konstruksi Rangka Batang Ruang Application of Bamboo Culm for Space Truss - Gina Bachtiar; Surjono Surjokusumo; Yusuf S Hadi; Naresworo Nugroho (Masyarakat Peneliti Kayu Indonesia, 2009)
Space truss is a three dimensional structure composed of short slender interconnected bars. The bars are selected to produce lightweight members. Since joints are frictionless pins, truss members carry out only axial force either tension or compression, without bending moment. Bamboo is a potential building material for this structure, because it is relatively light and high strength especially in tension. This research is aimed to develop bamboo joint that could carry out both tension and compression and it application in space truss for 3 m x 4 m simple roof structure.Connection designed using a taper rounded wooden plug attached to the inner part of bamboo and a tapered steel ring was used at the outside of the bamboo culm. Structural analysis using a program with finite element methods indicated that 4 cm diameter bamboo could use for 3 m x 4 m space truss with four supports, whereas for cantilever truss, the used of 4 cm diameter bamboo must be varied by using 6 cm diameter bamboo for elements that resist larger compression force.